Parental Influence and Perceptions: A Five-Year Exploration of School Readiness - Fehér, Ágnes Giczi Barnabásné; Vida, Gergő (Journal of Ecohumanism, 2024)
This study explores the influence of parental influence and perceptions on school readiness over the past five years. A systematic review of 720 items from Web of Science, Scopus, and ERIC databases yielded 13 relevant publications. The results highlight the impact of parental involvement, parenting style, and children's self-regulation skills on school readiness. Varied parental perspectives were found, with some prioritizing cognitive aspects and others emphasizing health, happiness, and social skills. Additionally, parents' perceptions were correlated with their level of independence and educational background influenced the perceived importance of cognitive skills. Emphasizing academic and behavioral skills before kindergarten correlated with higher academic achievement, self-regulation, and social skills in children. Negative influences on key competencies for school readiness included parental insensitivity, lack of warmth, maternal depression, children's negativity, insecure attachment, and parental incarceration. This recent research reinforces the importance of parental characteristics and perceptions in shaping school readiness activities with children.